Bobwhite and the "New" Biology - John L. Roseberry (National Quail Symposium Proceedings, 2017)
Phrases and concepts familiar to traditional wildlife managers like carrying capacity, annual surplus, and edge are being replaced in the literature and at conferences by terms such as biodiversity, metapopulations, and fragmentation. I raise the question of whether this new vocabulary merely represents trendy buzzwords of the 1980's, or is it relevant to bobwhite management in the 1990's and beyond? Some aspects of the “new” biology appear to differ from traditional wildlife management primarily with respect to scale, and may therefore be applicable in dealing with relatively isolated populations in dissected habitats. Others, however, reflect more basic differences in philosophies and agendas. Implications for future bobwhite management are discussed.
Keywords: conservation biology; landscape ecology; management; northern bobwhite